2002
DOI: 10.1061/(asce)0733-9496(2002)128:1(3)
|View full text |Cite
|
Sign up to set email alerts
|

Hydrologic Regionalization of Watersheds. I: Methodology Development

Abstract: A hydrologic regionalization scheme is proposed for classification of watersheds at gauged sites. This scheme used 16 streamflow parameters estimated by a time series model to classify 94 watersheds into 6 regions by cluster analysis. The classified regions seem to be separated by physiographical boundaries, especially the two main clusters. Discriminant analysis tests the significance of the cluster difference; thus, each cluster represents one hydrologic region. Principal component analysis interprets the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
1

Year Published

2007
2007
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(48 citation statements)
references
References 19 publications
0
47
0
1
Order By: Relevance
“…Information on the effect of complex driving factors on the hydrological response (not always easy to recognise) are in fact embedded in the temporal dynamics of the streamflow series (Chiang et al, 2002;Corduas, 2011). Important differences among the streamflow processes may be highlighted by the analysis of their temporal correlation structure, representable through the global autocorrelation function ACF (or the corresponding power spectrum).…”
Section: E Toth: Catchment Classificationmentioning
confidence: 99%
See 3 more Smart Citations
“…Information on the effect of complex driving factors on the hydrological response (not always easy to recognise) are in fact embedded in the temporal dynamics of the streamflow series (Chiang et al, 2002;Corduas, 2011). Important differences among the streamflow processes may be highlighted by the analysis of their temporal correlation structure, representable through the global autocorrelation function ACF (or the corresponding power spectrum).…”
Section: E Toth: Catchment Classificationmentioning
confidence: 99%
“…Since the time series autocorrelation functions might differ strongly one from another in shape, their comparison and classification through a visual inspection or a synthesising index is not straightforward. To tackle this issue, recent studies (De Thomasis and Grimaldi, 2001;Chiang et al, 2002;Grimaldi, 2004;Corduas, 2011) proposed to analyze the streamflow temporal dynamics through the parameter sets of linear models estimated on the corresponding streamflow time series. A more parsimonious, but less refined and necessarily approximated, approach is applied here for representing the autocorrelation structure: in addition to the lag-1 autocorrelation coefficient (previously used in regionalisation studies, for example, by Montanari and Toth (2007);Castiglioni et al (2010); Lombardi et al (2012) for the parameterisation of a rainfall-runoff model), it is here proposed to use an index representing the shape of the ACF, i.e.…”
Section: E Toth: Catchment Classificationmentioning
confidence: 99%
See 2 more Smart Citations
“…Regionalization is a useful technique in which hydrological knowledge at gauged sites is extrapolated to an ungauged site (Chiang et al, 2002). In recent years, a number of regionalization studies have been reported in the literature (Rao and Srinivas, 2006a;Parajka et al, 2007;Pinault and Allier, 2007;Isik and Singh, 2008;Oudin et al, 2008).…”
Section: Introductionmentioning
confidence: 99%